Aktywizacja zawodowa kobiet dojrzałych w kontekście koncepcji life long learning = Professional activation of mature women in the context of the life-long learning concept - Trzop, Beata; Witkiewicz, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the issue of women?s vocational and professional activation in Poland in relation to broadly defined modernization processes, and, as a result, to the already functioning solutions within social policy and programs for professional activation of mature women. The theoretical axis of the article is also the concept of lifelong learning. In aging societies, considering rapid technological, economic and cultural changes, this idea is designed to support individual and social group development through various forms, in a formal and informal manner.
Keywords: społeczeństwo starzejące się; uczenie się przez całe życie; aktywizacja zawodowa kobiet dojrzałych; aging society; life-long learning; professional activation of mature women